(untitled) (Orfeu, 2021)
Translation of the essay Les “hop” musicaux (The musical “hop”), written by Émile Jaques-Dalcroze and originally published in Le Rythme magazine (1930). The translation is preceded by a presentation on the origins and developments of the musical “hop”, one of the most important and ludic didactic principles of Dalcroze Eurhythmics, integrated with exercises in solfeggio, improvisation and living plasticity (“plastique animée”). At the end of the essay, to exemplify the use of the musical "hop", Dalcroze introduce a compendium of 55 exercises, a valuable material on a topic that has not been studied much in Brazil.